The Induction of Tolerance of Renal Allografts by Adoptive Transfer in Miniature Swine. Issue 5 (6th March 2013) - Okumi, M.; Scalea, J. R.; Gillon, B. C.; Tasaki, M.; Villani, V.; Cormack, T.; Hirakata, A.; Shimizu, A.; Sachs, D. H.; Yamada, K.
<x xml:space="preserve">Abstract</x> Our previous in vitro data have demonstrated that regulatory mechanisms are involved in tolerance of class I‐mismatched renal allografts in miniature swine treated with 12 days of high dose Cyclsporin A. In this study, we attempted to induce tolerance of class I‐mismatched kidneys by adoptive transfer of cells and/or kidneys from long‐term tolerant animals. Fifteen SLAdd miniature swine received 1.5 Gy whole body irradiation and class I‐mismatched (SLAgg) kidneys from naïve pigs with or without cotransplanted kidneys and/or adoptively transferred cells from long‐term tolerant (LTT) SLAdd recipients of SLAgg grafts. In addition, three SLAdd miniature swine received class I mismatched kidney with adoptively transferred cells from LTT SLAdd recipients. Naïve kidneys transplanted without a LTT kidney were rejected within 9 days. All recipients of naive kidneys along with cells and kidney grafts from LTT animals showed markedly prolonged survival of the naive renal grafts (day 28, >150 and >150 days). These studies suggest that (1) tolerated kidneys have potent regulatory effects and (2) cells from LTT animals infused in conjunction with kidney grafts augment these regulatory effects. To our knowledge, these studies represent the first demonstration of successful adoptive transfer of tolerance in large animals.